IMPLEMENTASI MODEL ALAT PENCEGAH KEHILANGAN BARANG PADA PUSAT PERBELANJAAN - puslit, Endah Setyaningsih; Hugeng, Hugeng; Antonius, Jeffry (Universitas Tarumanagara, 2007)
This paper discusses about the modeling scheme and implementation of security system to prevent losing goods at department store, and also to help coordination between security office with department store.